Unilateral versus bilateral endoscopic stenting in patients with unresectable malignant hilar obstruction: a systematic review and meta-analysis - Aghaie Meybodi, Mohamad; Shakoor, Delaram; Nanavati, Julie; Ichkhanian, Yervant; Vosoughi, Kia; Brewer Gutierrez, Olaya I.; Kalloo, Anthony N.; Singh, Vikesh; Kumbhari, Vivek; Ngamruengphong, Saowanee; Khashab, Mouen A. (Endoscopy International Open, 2020)
Background and study aims Endoscopic stent placement is used for palliative management of unresectable malignant hilar obstruction, which could be achieved by either unilateral or bilateral stent insertion.Materials and methods A literature search was performed to identify studies that reported outcomes of metallic biliary stent placement in patients with malignant hilar obstruction. Weighted pooled rates (WPR) along with 95 % confidence intervals (95 %CI) were calculated to determine and compare outcomes including technical and functional success, early and late adverse events, post procedure cholangitis, and stent occlusion between two groups.Results A total of 21 studies with 1292 patients were included. WPR of technical success was significantly higher in the unilateral group (97 %, 95 %CI: 93 –98 %) vs. bilateral group (89 %, 95 %CI: 84 –92 %) (P = 0.0.003). WPR for functional success in the unilateral and bilateral groups were 96 % (95 %CI: 91 –98 %) and 94 % (95 %CI: 91 –97 %), respectively (P = 0.48). The rate of early and late complications was comparable between the two groups.Conclusion In patients with unresectable malignant hilar obstruction, unilateral and bilateral metallic stenting techniques are comparable in terms of efficacy and safety.